INCIDENCE OF PREOPERATIVE ANEMIA IN PATIENT WITH GASTROINTESTINAL CANCER - Vân Anh, Trương; Thị Hoàng Phước, Nguyễn; Thị Oanh, Ngô (Journal of Health and Aging, 2025)
To evaluate the prevalence of preoperative anemia in patients with gastrointestinal cancer and assess the rate of anemia treatment prior to surgery. A prospective cross-sectional descriptive study with analytical components was conducted on patients with gastrointestinal cancer scheduled for elective surgery at Thong Nhat Hospital from January to October 2024. Preoperative anemia was observed in 49.2% of patients, with 72.4% of these cases occurring in elderly individuals (≥60 years old). Among the 58 patients diagnosed with anemia, 20.7% received preoperative iron supplementation, while 15.5% required blood transfusions before surgery. The prevalence of preoperative anemia in patients with gastrointestinal cancer is high, yet the rate of preoperative iron supplementation remains low. Routine screening and early intervention are essential to optimize hemoglobin levels prior to surgery and improve clinical outcomes.
Keywords: preoperative anemia; gastrointestinal cancer